Unity certified 3D artist courseware (Unity Technologies, 2019)
"Unity's only official series of courses to prepare for the Unity Certified 3D Artist exam. This specialization covers five topic areas distributed over 5 self-paced courses: Asset Creation and Management; Lighting, Reflection and Post-Processing Effect; Integrating Scripts for Scene Integrations; Character Setup; and Setting up Cutscenes. Participants in this specialization will complete multiple project milestones across two main projects: a Kitchen Configuration application with a realistic aesthetic, and a 3D video game level with a more stylized science-fantasy look. Across these two projects, learners will complete tasks including importing assets, manipulating materials, creating prefabs, adding lighting, setting up character models, and building cutscenes."--Resource description page